Using a Design-Based Research Study to Identify Principles for Training Instructors to Teach Online - Shattuck, Julie; Anderson, Terry (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Within the overall framework of design-based research, this paper reports on a study that focused on evaluating an online training course for online instructors. This intervention was designed as a possible solution to the problem facing some higher education institutions of how to provide quality, accessible training for mostly part-time instructors who are making the transition to teaching online. The research project explored whether the training course had any impact on the participants’ later teaching practice. The major outcome of this research study is the identification of design principles that can be used by other researchers and practitioners designing online instructor training.